The Serâbît Inscriptions: II. The Decipherment and Significance of the Inscriptions - Butin, Romain F. (Harvard theological review, 1928)
Beginning with Flinders Petrie scholars have been struck by the similarity between the script of these inscriptions and the Egyptian hieroglyphs. As the inscriptions were found in the neighborhood of numerous Egyptian monuments, an attempt was naturally made to read them as in the Egyptian language; but this proved unsuccessful, and it was evident that although the signs show close relationship with hieroglyphs, the language is not Egyptian. On Sinai, it was natural to think of a Semitic language. Further, the Egyptian phonetic value of the signs does not yield Semitic words, so that it appears that not only the language but the phonetic value of the signs is Semitic, not Egyptian.